Avaliação da estrutura interna do questionário Wheelchair Mobility Activity Log (WC-MAL) - Santos, Tainara Rodrigues dos (Universidade Federal de São Carlos, 2024)
Introduction: The effects of Spinal Cord Injury (SCI) include impairment of mobility, which requires the use of manual wheelchairs. Assessing the performance of wheelchair skills is essential since it is related to the quality of life of the wheelchair user. With this in mind, the Wheelchair Mobility Activity Log (WC-MAL) instrument was developed, which assesses the actual use of a manual wheelchair in people who have suffered an SCI. For the instrument to be more accurate, COSMIN recommends that its structural validity be measured. Objective: To assess the structural validity of the WC-MAL questionnaire applied to individuals with SCI and manual wheelchair users. Methods: A descriptive and quantitative cross-sectional study with a non-probabilistic convenience sample included 60 people diagnosed with SCI who use a manual wheelchair. The WC-MAL instrument was used to assess the actual mobility of wheelchair users using video calls. To assess the structural validity of the instrument, Rasch analysis was carried out, which evaluates the unidimensionality of the instrument's items and the relationship between them. The data collected was analyzed using Winsteps version 3.91.0. Results: By hierarchically ordering the items according to difficulty, it was observed that the easiest items were aligned with individuals with higher and more complete injuries, as well as with those who reported suffering shoulder pain, indicating low wheelchair skills. The more complex items, on the other hand, were commonly performed by individuals who had greater skills, in this case, individuals classified with lumbar and thoracic injuries. The DIF analysis found that the variables gender, level, and type of injury and shoulder pain could interfere with the responses and results of the instrument, representing a risk of bias. Items, where erratic or predictable behavior was observed in the Frequency, Performance, and Assistance scales, were excluded from the new version. No ceiling effect was observed; reliability and structural validity were adequate. Conclusion: The WC-MAL is suitable for assessing wheelchair performance by people with MSDs, but it was necessary to exclude items that did not fit the model. WC-MAL 2.0 was therefore prepared for publication.
Evaluation of the internal structure of the Wheelchair Mobility Activity Log (WC-MAL) questionnaire
Keywords: Medula espinal; Traumatismos da medula espinal; Cadeiras de rodas; Limitação da mobilidade; Spinal cord; Spinal cord injuries; Wheelchairs; Mobility limitation; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL